Sport-specific functional movement can simulate aspects of neuromuscular fatigue occurring in team sports - Wilke, J.; Fleckenstein, J.; Krause, F.; Vogt, L.; Banzer, W. (Sports Biomechanics, 2016)
Fatigue protocols have been used over the years to examine muscular exhaustion. As an alternative to approaches in laboratory settings, functional agility protocols claiming to mimic the multifaceted loads of athletic activity have been proposed. This study aimed to examine the effects of a functional agility short-term fatigue protocol (FAST-FP) on neuromuscular function. Twenty-eight healthy sports students (15 males, aged 24.3±2.4years) completed the FAST-FP, which consists of four components: three counter-movement jumps (90% of individual maximum), a 20-s bout of step-ups, three bodyweight squats and an agility run. Tasks were repeated until the participants no longer achieved the required jump height in two consecutive sets. Outcomes (pre-post) encompassed subjective exhaustion (visual analogue scale [VAS]), maximum isometric voluntary force of the knee extensors (MIVF), reactive strength index (RSI), mean power frequency (MPF, measured using surface electromyography) and maximum knee range of motion (ROM). Post-intervention, VAS (+54mm) increased significantly, while MIVF (-6.1%), RSI (-10.7%) and MPF (-4.1%) were reduced (p<0.05). No changes were observed for ROM (p>0.05). The FAST-FP induces small-to-moderate impairments in neuromuscular function and considerable self-perceived fatigue. Current evidence on exhaustion developing in team sports suggests that this magnitude of fatigue is similar. The protocol might thus be valuable in the evaluation of treatments counteracting post-match fatigue in team sports.